Glioblastomas, astrocytomas and oligodendrogliomas linked to Lynch syndrome. (19th January 2015) - Therkildsen, C.; Ladelund, S.; Rambech, E.; Persson, A.; Petersen, A.; Nilbert, M.
<x xml:space="preserve">Abstract</x> Background and purpose Brain tumors represent a rare and relatively uncharacterized tumor type in Lynch syndrome. Methods The national Danish Hereditary Nonpolyposis Colorectal Cancer Register was utilized to estimate the cumulative life‐time risk for brain tumors in Lynch syndrome, and the mismatch repair (MMR) status in all tumors available was evaluated. Results Primary brain tumors developed in 41/288 families at a median age of 41.5 (range 2–73) years. Biallelic MMR gene mutations were linked to brain tumor development in childhood. The risk of brain tumors was significantly higher (2.5%) in MSH2 gene mutation carriers compared to patients with mutations in MLH1 or MSH6. Glioblastomas predominated (56%), followed by astrocytomas (22%) and oligodendrogliomas (9%). MMR status was assessed in 10 tumors, eight of which showed MMR defects. None of these tumors showed immunohistochemical staining suggestive of the IDH1 R132H mutation. Conclusion In Lynch syndrome brain tumors occurred in 14% of the families with significantly higher risks for individuals with MSH2 gene mutations and development of childhood brain tumors in individuals with constitutional MMR defects.